The Moderating Effect of Audit Committee Meetings on The Relationship Between Internal Auditors’ Attributes and Financial Sustainability - Agyemang, Joseph Kwasi; Modisane, Cameron (Dinasti International Journal of Economics, Finance & Accounting, 2023)
The study aimed to establish the moderating effect of audit committee meetings on the relationship between internal auditors’ attributes and financial sustainability of municipalities. The study used census balanced panel data design and survey approach. The primary data was collected through 621 structured questionnaires distributed to chief audit executives and board of directors and audit committee chairpersons in 207 out of the 260 municipalities. The secondary data was collected from the Auditor General’s report. The study used panel data comprising both cross section and time series. The study sampled observations for a five-year period (from 2016 to 2020) with 1035 observations for 207 municipalities. Data collected were analysed using partial least square-structural equation modelling. The findings indicated that audit committee meetings, internal auditor independence, internal audit size with the exception of internal auditor competence, have direct significant influence on financial sustainability. However, audit committee meetings failed to significantly moderate the relationship between internal auditors’ attributes and financial sustainability.